2012
DOI: 10.1371/journal.pone.0032747
|View full text |Cite
|
Sign up to set email alerts
|

Perineuronal Nets Play a Role in Regulating Striatal Function in the Mouse

Abstract: The striatum is the primary input nucleus of the basal ganglia, a collection of nuclei that play important roles in motor control and associative learning. We have previously reported that perineuronal nets (PNNs), aggregations of chondroitin-sulfate proteoglycans (CSPGs), form in the matrix compartment of the mouse striatum during the second postnatal week. This period overlaps with important developmental changes, including the attainment of an adult-like gait. Here, we investigate the identity of the cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…More recent evidence indicates that WFA-labeled PNNs are associated with more heterogeneous neuronal phenotypes than previously thought, including several subgroups of interneurons, a small subset of cortico-cortical pyramidal cells, spinal cord motor neurons and cerebellum Purkinje cells (Ajmo et al, 2008; Brauer et al, 1995; Bruckner et al, 1993; Gati and Lendvai, 2013; Hartig et al, 1995; Pantazopoulos et al, 2006; Seeger et al, 1994; Wegner et al, 2003). Among these, GABAergic neurons undoubtedly represent one of the largest populations in several brain regions, including several cortical areas, striatum, hippocampus, inferior colliculus, septum and amygdala (Foster et al, 2014; Hartig et al, 1994; Lee et al, 2012; Pantazopoulos et al, 2006; Seeger et al, 1996; Shah and Lodge, 2013). As an example, in the amygdala of rhesus monkey, the overwhelming majority of WFA-positive PNNs ensheath neurons expressing glutamic acid decarboxylase (GAD), a typical marker for GABAergic neurons, with many of these neurons also expressing PVB and/or calbindin (Hartig et al, 1995).…”
Section: Perineuronal Nets: Composition and Association With Distimentioning
confidence: 99%
“…More recent evidence indicates that WFA-labeled PNNs are associated with more heterogeneous neuronal phenotypes than previously thought, including several subgroups of interneurons, a small subset of cortico-cortical pyramidal cells, spinal cord motor neurons and cerebellum Purkinje cells (Ajmo et al, 2008; Brauer et al, 1995; Bruckner et al, 1993; Gati and Lendvai, 2013; Hartig et al, 1995; Pantazopoulos et al, 2006; Seeger et al, 1994; Wegner et al, 2003). Among these, GABAergic neurons undoubtedly represent one of the largest populations in several brain regions, including several cortical areas, striatum, hippocampus, inferior colliculus, septum and amygdala (Foster et al, 2014; Hartig et al, 1994; Lee et al, 2012; Pantazopoulos et al, 2006; Seeger et al, 1996; Shah and Lodge, 2013). As an example, in the amygdala of rhesus monkey, the overwhelming majority of WFA-positive PNNs ensheath neurons expressing glutamic acid decarboxylase (GAD), a typical marker for GABAergic neurons, with many of these neurons also expressing PVB and/or calbindin (Hartig et al, 1995).…”
Section: Perineuronal Nets: Composition and Association With Distimentioning
confidence: 99%
“…Other evidence implicating PNNs in normal behavior stems from the colocalization of these structures in the striatum (Lee et al, 2012). Indeed, bilateral digestion of striatal PNNs was reported to increase both the width and variability of hind limb gait.…”
Section: The Role Of Pnns In Regulating Plasticitymentioning
confidence: 99%
“…Although their role is still not completely understood, PNNs have been implicated in ion homeostasis around highly active neurons (Bruckner et al, 1993; Bruckner et al, 1996a; Bruckner et al, 1996b; Hartig et al, 1999; Hartig et al, 2001; Hobohm et al, 1998) and neuroprotection (Bruckner et al, 1999; Cabungcal et al, 2013; Morawski et al, 2010; Morawski et al, 2012; Morawski et al, 2004; Schuppel et al, 2002). In addition, several studies have indicated that PNNs are important for memory and learning (Bruckner et al, 2000; Bukalo et al, 2001 Gogolla et al, 2009; Lee et al, 2012; Romberg et al, 2013; Saghatelyan et al, 2001). Moreover, PNNs appear to function in a multitude of key physiological processes during development, including the closure of the critical period (Bavelier et al, 2010; Friauf, 2000; Galtrey and Fawcett, 2007; Guimaraes et al, 1990; McRae et al, 2007; Miyata et al, 2012; Pizzorusso et al, 2002, 2006; Rauch, 2004)(Nabel and Morishita, 2013; Takesian and Hensch, 2013) as well as synaptic stability and plasticity (Dityatev and Schachner, 2003; Galtrey and Fawcett, 2007; Kwok et al, 2008; Pizzorusso et al, 2002, 2006; Wang and Fawcett, 2012)(Caroni et al, 2012), all factors that have been linked to schizophrenia pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of PNNs in the striatum (52), olfactory pathway (38, 76), basal ganglia (82), cerebellum (83), thalamus (56), visual cortex (27), insular cortex (50), high vocal center (49), orbital cortex (53), central auditory pathway (43, 84, 85), and spinal cord (86) suggests that the regulatory effects of PNNs are involved in a wide range of brain functions, including motor coordination, olfaction, procedural learning, voluntary motor movement, arousal state, vision, integration of cognitive, affective, sensory and autonomic information, vocal development, mediating decision making, processing of auditory stimuli, and nociception, respectively. Indeed, depletion or alterations in the molecular composition of PNNs induced by enzyme degradation (such as chondroitinase ABC, ChABC), by knock-out methods, or by clinical disease processes are associated with anomalies in sensory perception (67), impaired vision (71) as well as altered gait (52).…”
Section: The Role Of the Pnn In The Modulation Of Cognitive Functionmentioning
confidence: 99%
“…Indeed, depletion or alterations in the molecular composition of PNNs induced by enzyme degradation (such as chondroitinase ABC, ChABC), by knock-out methods, or by clinical disease processes are associated with anomalies in sensory perception (67), impaired vision (71) as well as altered gait (52). Conversely and perhaps surprisingly, global disruption of PNNs has been shown to significantly improve spatial learning (52), cognitive flexibility (87), recognition memory (54) and extinction training (51, 55). The neurobiological mechanism underlying these cognitive changes involves the PNNs that surround parvalbumin interneurons.…”
Section: The Role Of the Pnn In The Modulation Of Cognitive Functionmentioning
confidence: 99%